Intracranial self stimulation upregulates the expression of synaptic plasticity related genes and Arc protein expression in rat hippocampus. (20th August 2013) - Kádár, E.; Huguet, G.; Aldavert‐Vera, L.; Morgado‐Bernal, I.; Segura‐Torres, P.
Abstract : Post‐training lateral hypothalamus (LH) intracranial self stimulation (ICSS) has a reliable enhancing effect on explicit memory formation evaluated in hippocampus‐dependent tasks such as the Morris water maze. In this study, the effects of ICSS on gene expression in the hippocampus are examined 4.5 h post treatment by using oligonucleotide microarray and real‐time PCR, and by measuring Arc protein levels in the different layers of hippocampal subfields through immunofluorescence. The microarray data analysis resulted in 65 significantly regulated genes in rat ICSS hippocampi compared to sham, including cAMP‐mediated signaling as one of the most significantly enriched Database for Annotation, Visualization and Integrated Discovery (DAVID) functional categories. In particular, expression of CREB‐dependent synaptic plasticity related genes ( c‐Fos, Arc, Bdnf, Ptgs‐2 and Crem and Icer ) was regulated in a time‐dependent manner following treatment administration. Immunofluorescence results showed that ICSS treatment induced a significant increase in Arc protein expression in CA1 and DG hippocampal subfields. This empirical evidence supports our hypothesis that the effect of ICSS on improved or restored memory functions might be mediated by increased hippocampal expression of activity‐dependent synaptic plasticity related genes, including Arc protein expression, as neural mechanisms related to memory consolidation . Abstract : This report outlines three major observations regarding the molecular effects of ICSS memory‐facilitative treatment in rat hippocampus. A single LH‐ICSS session causes: (a) increases in the expression of IEGs related to synaptic plasticity and to learning and memory processes after 4.5 h; (b) the regulation of a subset of CREB family‐dependent genes (including c‐Fos, Arc, Bdnf, Ptgs‐2, Crem and Icer) in a time‐dependent manner following treatment administration; and (c) a significant induction, 4.5 h after administration, of Arc protein expression in CA1 and DG hippocampal subfields, revealing that ICSS specifically upregulates an effector protein related to morphological changes that underlie the synaptic modification involved in memory consolidation processes.